Exploring Genome-wide DNA Methylation Profiles Altered in Kashin-Beck Disease Using Infinium Human Methylation 450 Bead Chips - SHI, Xiao Wei; SHI, Bo Hui; LYU, Ai Li; ZHANG, Feng; ZHOU, Tian Tian; GUO, Xiong (Biomedical and environmental sciences, 2016)
To understand how differentially methylated genes（DMGs）might affect the pathogenesis of Kashin-Beck disease（KBD）.Genome-wide methylation profiling of whole blood from 12matched KBD and controls pairs was performed using a high-resolution Infinium 450 K methylation array.In total,97 CpG sites were differentially